1996
DOI: 10.1524/ract.1996.74.special-issue.321
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Geochemical Speciation Modelling to Predict the Impact of Uranium to Freshwater Biota

Abstract: Uranium is the prime potential contaminant in mine waste waters that may be released from the Ranger Uranium Mine (RUM) into the receiving waters of the Magela Creek, Alligator Rivers Region, Northern Australia. The potential ecological impact of the migration of uranium, that would result from an elevation in its concentration above background, in the Magela Creek downstream of the RUM, has been experimentally investigated by integrating biomonitoring with geochemical speciation modelling. The freshwater biva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 11 publications
1
30
0
1
Order By: Relevance
“…2). The formation of U complexes with HS generally decreases, with increasing U concentration, once the binding saturation of the HS by U is reached [75]. Uranyl-carbonate and uranyl-hydroxide-carbonate species become more important than uranyl complexes with HS as the hardness, alkalinity, and pH of the water increase (usually > pH 7) [73].…”
Section: Speciation Freshwatermentioning
confidence: 99%
See 1 more Smart Citation
“…2). The formation of U complexes with HS generally decreases, with increasing U concentration, once the binding saturation of the HS by U is reached [75]. Uranyl-carbonate and uranyl-hydroxide-carbonate species become more important than uranyl complexes with HS as the hardness, alkalinity, and pH of the water increase (usually > pH 7) [73].…”
Section: Speciation Freshwatermentioning
confidence: 99%
“…Markich et al [75] found that a fivefold increase in the bicarbonate concentration of synthetic Magela Creek water, at a fixed pH (5) and water hardness (3.5 mg CaCO 3 l -1 ), resulted in a 20% reduction in the toxicity (DVO) of U to V. angasi. The decrease in U toxicity corresponded to a similar factor of decrease in the calculated percentages of UO 2 2+ and UO 2 OH + , or an increase in UO 2 CO 3 due to UO 2 2+ complexation with carbonate.…”
Section: Effects Of Carbonate and Phosphatementioning
confidence: 99%
“…Several studies (e.g., Manley and Davenport, 1979;Kramer et al, 1989;Huebner and Pynnönen, 1992;Markich et al, 1996;Fdil et al, 2006;Schwartzmann et al, 2011) have confirmed that valve movement behavior can be used to sensitively quantify biological reactions in real-time (Figure 10) for assessing the toxicological effects of metal exposures. The observations found that upon exposure to toxic concentrations of metals, bivalves have the ability to reduce the exposure of their soft tissues for extended periods by closing their valve (Manley and Davenport, 1979;Kramer et al, 1989;Salánki and Balogh, 1989;Huebner and Pynnönen, 1992).…”
Section: Future Application Approachesmentioning
confidence: 97%
“…This is highly unlikely and leads us to believe that uranium uptake does not comply to the FIM of metal bioavailability. More than one transport mechanism (facilitated diffusion of the free uranyl ion) might contribute to uranium intake: i) The facilitated diffusion of hydroxo-complexes [15]; or ii) The passive diffusion of neutral lipophilic complexes such as U02(OH)2° (.e.g. analogue to HgCl 2° movement across membranes [16]).…”
Section: Concentration Dependence Of Uranium Uptake and Adsorptionmentioning
confidence: 99%
“…However, a number of intriguing experiments have been reported in the literature where the metal's "residual" bioavailability in the presence of hydrophilic MIv complexes has been found to exceed that which would have been predicted on the basis of the free-metal ion concentration at equilibrium [2]. Such intriguing results have been reported for U toxicity (valve movement response) toward the bivalve, Velesunio angasi, in laboratory exposure experiments [3]. Increasing pH from 5.0 to 6.0 decreased uranium toxicity, however, this amelioration could not be solely related to the decrease in {U0 2 2+ } within this range.…”
Section: Introductionmentioning
confidence: 99%